2014
DOI: 10.1007/s10865-014-9578-1
|View full text |Cite
|
Sign up to set email alerts
|

Psychological states, serum markers and survival: associations and predictors of survival in patients with renal cell carcinoma

Abstract: This study sought to determine if there was an association between prognostic-based serum biomarkers, survival, and psychosocial factors in patients with meta-static renal cell carcinoma. Associations were found between psychosocial factors and biomarker levels (hemoglobin with depressive symptoms (r = −0.29), positive affect (r = 0.30), social support (r = 0.19), and perceived stress (r = −0.27); albumin with depressive symptoms (r = −0.19), positive affect (r = 0.22), and social support (r = 0.20); alkaline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…Surprisingly, there are few published studies of PA and recurrence, progression, or mortality among people with cancer. In a recent study of patients with metastatic renal cell carcinoma (Prinsloo et al 2015), the PA subscale of the CES-D predicted longer survival. Notably, survival was better for patients who had both high PA and lower depressive symptoms, supporting the importance of looking at both valences together.…”
Section: Hivmentioning
confidence: 94%
“…Surprisingly, there are few published studies of PA and recurrence, progression, or mortality among people with cancer. In a recent study of patients with metastatic renal cell carcinoma (Prinsloo et al 2015), the PA subscale of the CES-D predicted longer survival. Notably, survival was better for patients who had both high PA and lower depressive symptoms, supporting the importance of looking at both valences together.…”
Section: Hivmentioning
confidence: 94%
“…[7][8][9] To the best of our knowledge, the role of positive affect in patients with cancer has been less well characterized. One study found that positive affect was related to biomarkers and survival in patients with renal cell carcinoma, 10 whereas another found detrimental effects of positive affect on inflammatory biomarkers. 11 Other studies have shown that eudaimonic well-being, or experiencing a deeper sense of meaning in life, fulfilling one's potential, and accepting oneself, 12 is distinct from positive affect and may be a stronger predictor of health status.…”
Section: Introductionmentioning
confidence: 99%
“…As might be expected, patients diagnosed with metastatic cancer, regardless of type, tend to report high levels of distress, with subsequent impairment in QoL, worse clinical outcomes, and increased health care resource utilization [3,18]. Fear of cancer recurrence/progression is also an important contributor and has been associated with greater distress [19].…”
mentioning
confidence: 93%